A technique of dispatching algorithms for web-server cluster - Zarina Mohamad (Fakulti Sains dan Teknologi, 2011)
Providing reliable and efficient services are primary goals in designing a web server cluster (WSC). Data replication techniques can be used to improve the reliability of the system. One of the techniques is Neighbor Replica Distribution Technique (NRDT). Domain Name Server (DNS) is one of the software used for managing request information from users.